Association between cigarette use and adolescents’ behavior - Cruz,Jamile Francelino (2020)
ABSTRACT OBJECTIVE To determine the prevalence of cigarette use among adolescents and to identify associated health risk behaviors. METHODS This is a cross-sectional study with a representative sample, composed of 1059 adolescents between 13 and 19 years old, enrolled in primary and secondary public schools of Olinda, Pernambuco, in 2014. Information was obtained through self-administered questionnaires (validated version of YRBS 2007). Cigarette experimentation was defined as smoking at least once in life. Adolescents who smoked at least one day within 30 days prior to the survey were considered current smokers. Most students were female and 16 years old or older. RESULTS Almost 30% used it in life and about 10% smoked within the 30 days before the survey. Suicidal ideation (PR = 1.51, 95%CI 1.25–1.82), alcohol use (PR = 1.41, 95%CI 1.03–1.92), marijuana (PR = 1.64, 95%CI 1.37–1.96), excessive alcohol consumption (PR = 1.57, 95%CI 1.15–2.16) and sexual experience (PR = 1.78, 95%CI 1.43–2.21) have increased the risk of using cigarettes. Feelings of sadness (PR = 1.70, 95%CI 1.22–2.36), alcohol use (PR=2.40, 95%CI 1.12–5.12), excessive alcohol consumption (PR = 2.5, 95% CI 1.24–5.38), marijuana (PR = 2.31, 95%CI.57–3.39) and cocaine (PR = 1.99, 95%CI.32–3.01) increased the risk of cigarette use within the 30 days before the survey. CONCLUSIONS Cigarette use among adolescents from Olinda was high, being considered higher than the national prevalence. Possible factors associated with cigarette use were drug use (alcohol, marijuana, and cocaine) and behaviors related to sexual experience, feelings of sadness and suicidal ideation.